2016
DOI: 10.1016/j.otsr.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Return to recreational sport and clinical outcomes with at least 2 years follow-up after arthroscopic repair of rotator cuff tears

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…A total of 108 partial articular supraspinatus tendon avulsions were reported; 42 tears out of the entire patient cohort had an unspecified tendon; and no bursal-sided partial tears were reported. Twelve studies 2-6,8,9,14,15,23,25,27 reported concomitant procedures for 341 patients, with the most common being subacromial decompression and acromioplasty (n = 151), subacromial decompression (n = 108), biceps tenotomy (n = 93), biceps tenodesis (n = 59), SLAP repairs (n = 47), and anterior or posterior labral repair (n = 34). Three studies 2,8,15 used a double-row repair; 6 studies, 6,9,11,14,22,25 a single-row repair; and 6 studies, 3-5,21,23,27 both techniques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 108 partial articular supraspinatus tendon avulsions were reported; 42 tears out of the entire patient cohort had an unspecified tendon; and no bursal-sided partial tears were reported. Twelve studies 2-6,8,9,14,15,23,25,27 reported concomitant procedures for 341 patients, with the most common being subacromial decompression and acromioplasty (n = 151), subacromial decompression (n = 108), biceps tenotomy (n = 93), biceps tenodesis (n = 59), SLAP repairs (n = 47), and anterior or posterior labral repair (n = 34). Three studies 2,8,15 used a double-row repair; 6 studies, 6,9,11,14,22,25 a single-row repair; and 6 studies, 3-5,21,23,27 both techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of patient satisfaction was reported in 6 studies. 3,5,6,14,21,27 Bhatia et al 5 reported a median postoperative satisfaction score of 10 on a scale from 1 to 10. One study 21 indicated 100% satisfaction in everyday activities, and another 6 had a 98% overall satisfaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the published literature concerning active patients has focused on returning to preoperative activities, [3][4][5]24,27,48 and very few radiographic or detailed functional data concentrating on the effect of postoperative activities have been reported. 2,31 Owing to this lack of information, outcome-based guidelines for active patients, in terms of postoperative activity level management, are unavailable.…”
mentioning
confidence: 99%
“…Rotator cuff pathology is one of the most commonly encountered orthopaedic problems, with an estimated prevalence of 17% to 35% including asymptomatic patients[ 1 ]. In symptomatic patients, rotator cuff repair (RCR) usually provides good to excellent clinical outcomes[ 1 - 4 ]. As a result, RCR has become one of the most frequently performed orthopaedic procedures during the last two decades[ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%